I can see clearly now: Clarity of transgression-related motivations enhances narcissists' lack of forgiveness. (15th January 2017) - Fatfouta, Ramzi; Schröder-Abé, Michela
Abstract: Past research has revealed that narcissists lack forgiveness. However, little is known about factors that might either buffer or, more critically, enhance the link between narcissism and lack of forgiveness. To address this gap in the literature, the present studies focused on the moderating role of clarity of transgression-related motivations. In an original and a replication study ( N s = 509 and 532, respectively), participants rated their levels of narcissistic admiration and rivalry and recalled a personal episode in which someone had hurt them. Subsequently, participants reported on their lack of forgiveness toward their transgressor. Response speed to these ratings served as an indirect clarity measure, with faster responses indicating greater clarity. In both studies, narcissistic rivalry (but not admiration) was positively related to lack of forgiveness and this relationship was stronger among individuals who were clear about their transgression-related motivations. Results inform our understanding of socio-emotional factors that contribute to narcissists' lack of forgiveness following interpersonal hurt. Graphical abstract: Highlights: Examined relations between narcissistic admiration/rivalry and lack of forgiveness Clarity of transgression-related motivations acted as a moderator. Rivalry (but not admiration) was positively related to lack of forgiveness. This relationship was stronger among individuals high (vs. low) in clarity. Importance of socio-emotional factors in the narcissism/lack of forgiveness link